2017
DOI: 10.1074/jbc.m117.794461
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporter 2 interacts with vacuolar ATPase and is required for polarization, vesicle acidification, and secretion in mammary epithelial cells

Abstract: An important feature of the mammary gland is its ability to undergo profound morphological, physiological, and intracellular changes to establish and maintain secretory function. During this process, key polarity proteins and receptors are recruited to the surface of mammary epithelial cells (MECs), and the vesicle transport system develops and matures. However, the intracellular mechanisms responsible for the development of secretory function in these cells are unclear. The vesicular zinc (Zn) transporter ZnT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 100 publications
(114 reference statements)
5
40
0
Order By: Relevance
“…This finding highlights the fact that during lactation in which ZnT2 expression is markedly induced, an intricate balance between the overexpression of vesicular ZnT2 and V-ATPase must be maintained in order to ensure that the acidic pH is maintained by V-ATPase as otherwise, alkalization will result in loss of the proton-motive force and consequent disruption of multiple vesicular secretory functions. In support of this hypothesis is a recent paper by Lee et al, [58] which showed that during lactation in a mouse model, the protein levels of V-ATPase are markedly elevated in mammary gland epithelial cells. This of course highlights the obligatory balance between overexpressed ZnT2 (as well as other transporters) which translocates protons to the cytoplasm during vesicular accumulation of zinc (and other physiological substrates) and proper V-ATPase levels.…”
Section: Discussionmentioning
confidence: 76%
“…This finding highlights the fact that during lactation in which ZnT2 expression is markedly induced, an intricate balance between the overexpression of vesicular ZnT2 and V-ATPase must be maintained in order to ensure that the acidic pH is maintained by V-ATPase as otherwise, alkalization will result in loss of the proton-motive force and consequent disruption of multiple vesicular secretory functions. In support of this hypothesis is a recent paper by Lee et al, [58] which showed that during lactation in a mouse model, the protein levels of V-ATPase are markedly elevated in mammary gland epithelial cells. This of course highlights the obligatory balance between overexpressed ZnT2 (as well as other transporters) which translocates protons to the cytoplasm during vesicular accumulation of zinc (and other physiological substrates) and proper V-ATPase levels.…”
Section: Discussionmentioning
confidence: 76%
“…Like Zinc, AMPK functions as a double-edged sword in the axis of cell survival-death ( Ronnett et al, 2009 ). In case of chronic neurodegenerative diseases such as Alzheimer’s or Parkinson’s disease, physiological levels of zinc or AMPK activity may promote cell survival through the enhancement of lysosomal function and the resultant reduction of protein aggregates accumulation ( Park et al, 2011 ; Lee et al, 2017 ; Jang et al, 2018 ). However, in cases of acute brain injury, excessive zinc influx, and the resultant pathological AMPK activation may trigger cell death ( Eom et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase of free zinc in the lysosome induces lysosomal acidification and activates lysosomal enzymes such as cathepsins. In most cases, these changes promote cell survival (Park et al, 2011;Seo et al, 2015;Lee et al, 2017). However, a high concentration of extracellular zinc enters the cytosol through voltage-gated calcium channel (VGCC), calcium-permeable AMPA receptor (AMPA-R), or NMDA-R, and then lysosomes or mitochondria likely via zinc transporters (Sensi and Jeng, 2004).…”
Section: A Possible Therapeutic Approach Against Ischemic Stroke Withmentioning
confidence: 99%
“…Two-way ANOVA indicated statistically significant differences both by tissue and by genotype; asterisks denote difference between genotypes for any given tissue from a Tukey's post hoc analysis. Overend et al, 2016;Tognon et al, 2016) does not provide a thermodynamic explanation how ZnT35C accumulates zinc in storage granules as would be the current thinking in the field (Jeong and Eide, 2013;Kambe et al, 2017;Lee et al, 2017b), the alternative hypothesis would be that the ATPase activity of the ABCG2 homologues white and scarlet are implicated in zinc transport, perhaps working in a similar way to K ATP channels (Lee et al, 2017a), i.e. by forming a pump in complex with ZnT35C.…”
Section: On the Function Of The Abcg2 Transportersmentioning
confidence: 97%